Mitochondrial Phenotype as a Driver of the Racial Dichotomy in Obesity and Insulin Resistance - Jevtovic, Filip; Krassovskaia, Polina M.; Lopez, Christian A.; Fisher-Wellman, Kelsey H.; Cortright, Ronald N.; Broskey, Nicholas T. (Biomedicines, 2022)
African Americans (AA) are disproportionately burdened by metabolic diseases. While largely unexplored between Caucasian (C) and AA, differences in mitochondrial bioenergetics may provide crucial insight to mechanisms for increased susceptibility to metabolic diseases. AA display lower total energy expenditure and resting metabolic rate compared to C, but paradoxically have a higher amount of skeletal muscle mass, suggestive of inherent energetic efficiency differences between these races. Such adaptations would increase the chances of overnutrition in AA; however, these disparities would not explain the racial difference in insulin resistance (IR) in healthy subjects. Hallmarks associated with insulin resistance (IR), such as reduced mitochondrial oxidative capacity and metabolic inflexibility are present even in healthy AA without a metabolic disease. These adaptations might be influential of mitochondrial “substrate preference” and could play a role in disproportionate IR rates among races. A higher glycolytic flux and provision of shuttles transferring electrons from cytosol to mitochondrial matrix could be a contributing factor in development of IR via heightened reactive oxygen species (ROS) production. This review highlights the above concepts and provides suggestions for future studies that could help delineate molecular premises behind potential impairments in insulin signaling and metabolic disease susceptibility in AA.